The prevalence of esophageal cancer after caustic and pesticide ingestion: A nationwide cohort study - Mu, Han-Wei; Chen, Chun-Hung; Yang, Kai-Wei; Pan, Chi-Syuan; Lin, Cheng-Li; Hung, Dong-Zong (PloS one, 2020)
Habits such as smoking and alcohol drinking and existing esophageal malfunction are considered the main risk factors for esophageal carcinogenesis. Caustic ingestion of acidic or alkaline agents or strong irritants can induce severe esophageal corrosive injury and increase esophageal cancer risk. We studied the relationship between esophageal carcinoma and acute detergent or pesticide poisoning by using nationwide health insurance data. Methodology/Principle findings : We compared a pesticide/detergent intoxication cohort (N = 21,840) and an age- and gender-matched control cohort (N = 21,840) identified from the National Health Insurance Research Database between 2000 and 2011. We used the multivariable Cox proportional model to determine esophageal carcinoma risk. The overall incidence density of esophageal cancer was 1.66 per 10,000 person-years in the comparison cohort and 4.36 per 10,000 person-years in the pesticide/detergent intoxication cohort. The corresponding adjusted hazard ratio (HR) for esophageal cancer was 2.33 (95% confidence interval [CI] = 1.41–3.86) in the pesticide/detergent intoxication cohort compared with the control cohort. Patients with corrosive and detergent intoxication did not have a higher risk of esophageal cancer (adjusted HR = 0.98, 95% CI = 0.29–3.33) than those without pesticide/detergent intoxication. However, patients with pesticide intoxication had a significantly higher risk of esophageal cancer (adjusted HR = 2.52, 95% CI = 1.52–4.18) than those without pesticide/detergent intoxication. Conclusion : In the present study, after adjusting for conventional risk factors, we observed that pesticide intoxication could exert substantial effects through increased esophageal cancer risk. However, patients with detergent intoxication may not have an increased risk of esophageal cancer.